On offer to Ontario consumers three years after legalization: A profile of cannabis products, cannabinoid content, plant type, and prices - Tassone, Felicia; Di Ciano, Patricia; Liu, Yuxin; Rueda, Sergio (Frontiers in Psychiatry, 2023)
Cannabis was legalized in Canada in October 2018, regulating the production, distribution, sale, and possession of dried cannabis and cannabis oils. Additional products were legalized one year later, including edibles, concentrates, and topicals, with new lines of commercial products coming to market. Ontario is the most populous province in Canada and has the largest cannabis market with the highest number of in-person retail stores and the most cannabis products available online. This study aims to create a profile of products available to consumers three years after legalization by summarizing types of products, THC and CBD potency, plant type, and prices of product sub-categories. We extracted data from the website of the Ontario Cannabis Store (OCS)—the public agency overseeing the only online store and sole wholesaler to all authorized in-person stores—in the first quarter of 2022 (January 19-March 23). We used descriptive analyses to summarize the data. A total of 1,771 available products were mapped by route of administration into inhalation (smoking, vaping, and concentrates), ingestible (edibles, beverages, oils, and capsules) and topical. Most inhalation products included ≥ 20 %/g THC (dried flower: 94%; cartridges: 96%; resin:100%) while ingestible products had similar proportions of THC and CBD content. Indica-dominant products tend to be more prominent in inhalation products while sativa-dominant products tend to be more prominent in ingestible products. The average sale price of cannabis was 9.30 $/g for dried flower, 5.79 $/0.1g for cartridges, 54.82 $/g for resin, 3.21 $/unit for soft chews, 1.37 $/ml for drops, 1.52 $/unit for capsules, and 39.94 $/product for topicals. In summary, a wide variety of cannabis products were available to Ontarians for different routes of administration and provides numerous indica-dominant, sativa-dominant, and hybrid/blend options. The current market for inhalation products however is geared towards the commercialization of high-THC products.